2016
DOI: 10.3897/zookeys.606.9310
|View full text |Cite
|
Sign up to set email alerts
|

A new solitary free-living species of the genus Sphenopus (Cnidaria, Anthozoa, Zoantharia, Sphenopidae) from Okinawa-jima Island, Japan

Abstract: A new species of free-living solitary zoantharian is described from Okinawa, Japan. Sphenopus exilis sp. n. occurs on silty seafloors in Kin Bay and Oura Bay on the east coast of Okinawa-jima Island. Sphenopus exilis sp. n. is easily distinguished from other Sphenopus species by its small polyp size and slender shape, although there were relatively few differences between Sphenopus exilis sp. n. and Sphenopus marsupialis in the molecular phylogenetic analyses. Currently, very little is known about the ecology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recent molecular work has also indicated that this this genus-group may form a clade with some Palythoa spp. (Reimer et al 2012b, Fujii and Reimer 2016). …”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular work has also indicated that this this genus-group may form a clade with some Palythoa spp. (Reimer et al 2012b, Fujii and Reimer 2016). …”
Section: Systematicsmentioning
confidence: 99%
“…Article 23.9.1.2 of the Code is fulfilled as the family-group name Sphenopidae Hertwig, 1882, is in current and widespread usage, as evidenced by the 30 publications by 99 different authors over the past 34 years using Sphenopidae as a valid name for the taxon it denotes (viz., Nagabhushanam and Jothinayagam 1982: 17; Ryland et al 2000: 191, 192; Ryland and Lancaster 2003: 407, 409, 415; Ryland and Lancaster 2004: 180; Ryland and Westphalen 2004: 411; Ryland et al 2004: 1195, 1197; Acosta et al 2005: 147–149, 151, 154, 160; Sinniger et al 2005: 1122, 1125, 1126; Daly et al 2007: 144; Sinniger et al 2008: 1254, 1256, 1257; Fautin and Daly 2009: 356; Del Mónaco et al 2010: 360; Reimer and Sinniger 2010: 251; Reimer et al 2010c: 606, 616; Swain 2010: 2592; Reimer et al 2011a: 983, 985, 987, 989, 991, 992; Cavallari et al 2012: 25; Longo et al 2012: [1]; Palmer et al 2012: 3880; Reimer et al 2012b: 43, 45, 47, 49; Rodríguez-Viera et al 2012: 32; Costello et al 2013: [2]; Fujii and Reimer 2013: 510, 516; Krishna and Gophane 2013: 210; Koupaei et al 2014: 64; Alencar et al 2015: 1113, 1114, 1121; Irei et al 2015: 1, 2, 4, 6, 14–16, 20; Qin et al 2015: 100; De la Cruz-Francisco et al 2016: 24; Fujii and Reimer 2016: 11, 12, 14, 17, 19, 20; Risi and Macdonald 2016: 113).…”
Section: Synonyms Of Epizoanthus Gray 1867 (Epizoanthidae) (I): Cortmentioning
confidence: 99%
“…Recent investigations by SCUBA diving have revealed many undescribed benthic invertebrate species from the subtidal zone, usually in depths greater than 10 m, especially in the Ryukyu Islands, southwestern Japan (e.g., Kise et al 2017;Naruse and Yoshida 2018). In this area, many new records and species of marine benthos from depths of 15-40 m have recently been described (e.g., Obuchi et al 2009;White and Reimer 2012;Fujii and Reimer 2016;Lau et al 2019). In contrast, benthic fauna of the Amamioshima island which is the second-biggest island within the Ryukyu Islands, and neighboring Kakeromajima, Ukejima and Yorojima islands (in this study, these four islands are referred "Amami-oshima island group"; Fig.…”
Section: Introductionmentioning
confidence: 99%